Percentage of Parent Stock Chicken Eggs with Thin Shells in Battery Cage and Postal Cage Maintenance Methods at Farm Cariu Bogor - Anggri Septiana; Miyayu Soneta Sofyan; Anwar Ma'ruf; M. Gandul Atik Yuliani (Journal of Applied Veterinary Science And Technology, 2022)
Background: In the maintenance of parent stock chicken, egg production is the main thing to consider because this will produce quality DOC chickens. In this case, the eggshell affects the hatchability of eggs, affecting the egg productivity level. Purpose: To determine the effect of differences in cage maintenance methods on the case of eggs with thin shells. Eggs with thin shells affect the hatchability of eggs in incubators which causes a decrease in egg and saleable chick production. Methods: The method used is primary and secondary data collection, recording eggs for three weeks to determine the number of eggs with thin shells daily in postal and battery cages. Results: In postal cages, the percentage yield was higher for the number of eggs with thin shells than in battery cages, which was about 0.52%, while in battery cages, it was 0.21%. The cause of the high percentage of cases of eggs with thin shells in postal cages is the chickens' direct contact with the litter. Poor litter conditions and rarely replaced cause the accumulation of dirt. The manure will ferment with husks and generate higher ammonia levels in the postal cage, causing disturbances in egg production, one of which is causing the eggshell to become thin. Conclusion: In this study, the shape of the cage floor was one of the factors causing the percentage of eggs with thin shells in the postal cage form that used litter as a base had a higher percentage of eggs with thin shells compared to battery cages.